2013
DOI: 10.1192/pb.bp.112.039933
|View full text |Cite
|
Sign up to set email alerts
|

Crisis teams: systematic review of their effectiveness in practice

Abstract: Aims and methodCrisis resolution and home treatment teams (variously abbreviated to CRTs, CRHTTs, HTTs) were introduced to reduce the number and duration of in-patient admissions and better manage individuals in crisis. Despite their ubiquity, their evidence base is challengeable. This systematic review explored whether CRTs: (a) affected voluntary and compulsory admissions; (b) treat particular patient groups; (c) are cost-effective; and (d) provide care patients value.ResultsCrisis resolution teams appear ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 35 publications
1
38
0
7
Order By: Relevance
“…The tentative conclusion reached in recent systematic reviews was that CRTs are effective in reducing inpatient admissions (9,10). For this conclusion to be supported in the current study, the reduced emergency response in the community would have needed to have resulted in a meaningful increase in admissions to the inpatient units.…”
Section: Discussionmentioning
confidence: 60%
“…The tentative conclusion reached in recent systematic reviews was that CRTs are effective in reducing inpatient admissions (9,10). For this conclusion to be supported in the current study, the reduced emergency response in the community would have needed to have resulted in a meaningful increase in admissions to the inpatient units.…”
Section: Discussionmentioning
confidence: 60%
“…They were designed as ward 'gatekeepers', providing intensive short-term care to vulnerable patients considered for admission or discharge 3 . CRTs provide multi-disciplinary interventions, including assessment and engagement of patients in crisis, psychological support and education, medication review and administration, and social support and advocacy 4 . In 2000, only a few areas of the UK were covered by CRTs, but they are now available in most Trusts in the UK 5 , and have similarly become an integral part of community care in a number of settings internationally, for example in Norway 6 and Germany…”
Section: Introductionmentioning
confidence: 99%
“…There are undoubted methodological difficulties in undertaking research in this field, and it has long been identified that PP does not lend itself to the scientific gold standard of the double-blind randomized controlled trial. However, this is a problem shared by research in many areas of mental health such as how to reduce suicidal behaviour, and the effectiveness of assertive outreach or crisis and home treatment teams (Carpenter et al, 2013). Furthermore other NICE-recommended psychological (Lynch et al, 2010) and current pharmacological (Caddy et al, 2014, in press;Penn & Tracy, 2012;Sendt et al, 2012) treatments of mental illness are hardly optimal, with outcome data underwhelming and many individuals suffering enduring problems with the indirect costs to the person and society that such difficulties inevitably bring: nevertheless the data, of varying methodological quality and impressiveness, is there in greater numbers than for PP.…”
Section: Discussion: What Next For Psychoanalytic Psychotherapy and Pmentioning
confidence: 99%